Innovative Use of Spirogyra sp. Biomass for the Sustainable Adsorption of Aflatoxin B1 and Ochratoxin A in Aqueous Solutions - Wipada Siri-anusornsak; Oluwatobi Kolawole; Siriwan Soiklom; Krittaya Petchpoung; Kannika Keawkim; Chananya Chuaysrinule; Thanapoom Maneeboon (Molecules)
This research investigates the efficacy of Spirogyra sp. biomass as an effective adsorbent for the removal of AFB1 and OTA from aqueous solutions. Several factors, including contact time, adsorbent dosage, pH level, and initial mycotoxin concentration, were analyzed to evaluate their impact on adsorption efficacy. The optimal contact time for equilibrium was determined at 60 min, during which the TPA obtained a 91% reduction in AFB1 and 68% removal of OTA. Although increasing the adsorbent dosage improved effectiveness, excessive quantities led to particle aggregation, hence diminishing adsorption performance. The optimal dosage of 5.0 mg/mL optimized the efficacy and use of resources. Adsorption was more efficacious at acidic to neutral pH levels (5–6), enhancing the accessibility of functional groups on the biomass. Kinetic analysis indicated that adsorption process followed a pseudo second-order model, whereas isotherm studies demonstrated a heterogeneous adsorption mechanism, with the Freundlich model providing the optimal fit. The TPB exhibited enhanced adsorption capacities for both mycotoxins, offering a viable solution for mitigating mycotoxin contamination in food and feed. These findings illustrate the significance of biomass treatment techniques in improving mycotoxin removal efficacy and suggest the potential of algal biomass in food safety applications.